Hubungan Aktivitas dan Respon terhadap Hasil Belajar Program Linier Setelah Diterapkan Pembelajaran Genius Learning pada Program Studi Pendidikan Matematika - Muchtadi, Muchtadi; Hartono, Hartono; Oktaviana, Dwi (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2017)
This research aimed to know the correlation of activity and response to the learning outcomes of linear program after applied learning genius learning on mathematics education program. The research method used is quantitative with the form of quasi-experimental research. The population of this study is all students of the sixth semester with a sample of one class obtained using cluster random sampling technique. The result of data analysis shows that there is a significant relationship between learning activities and responses to student learning outcomes after applied learning genius learning. Student learning activities make a significant contribution to student learning outcomes after the learning of genius learning is applied. Students responses make a significant contribution to student learning outcomes after the learning of genius learning is applied.